Effect of Aerosolization and Drying on the Viability of Pseudomonas syringae Cells - Alsved, Malin; Holm, Stine; Christiansen, Sigurd; Smidt, Mads; Rosati, Bernadette; Ling, Meilee; Boesen, Thomas; Finster, Kai; Bilde, Merete; Löndahl, Jakob; Šantl-Temkiv, Tina (Frontiers in Microbiology, 2018)
Airborne dispersal of bacterial cells influences microbial biogeography, gene flow, atmospheric processes, human health, transmission of diseases and agriculture. The extent of this impact depends essentially on cell-survival rates during the process of aerosolization. A central factor for cell-survival is water availability prior to and upon aerosolization and the ability of cells to successfully cope with the drying stress determines their chances of survival. In this study, we used the ice-nucleation active, plant pathogenic Pseudomonas syringae strain R10.79 as a model organism to investigate the effect of drying on cell survival. Two forms of drying were simulated: drying of cells in small droplets aerosolized from a wet environment by bubble bursting and drying of cells in large droplets deposited on a surface. For drying of cells both in aerosol and surface droplets, the relative humidity was varied in the range between 10% and 90%. The fraction of surviving cells was determined by live/dead staining followed by flow cytometry. We also evaluated the effect of salt concentration in the droplets on the survival of drying cells, by varying the ionic strength between 0 and 700 mM using NaCl and sea salt. For both aerosol and surface drying, cell survival increased with decreasing relative humidity (p<0.01), and for surface drying, survival was correlated with increasing salt concentration (p<0.001). Imaging of cells with TEM showed shrunk cytoplasm and cell wall damage for a large fraction of aerosolized cells. We observed a 10-fold higher fraction of surviving cells when dried as aerosol compared to when dried on a surface, thus this study suggests a potentially higher survival of bacteria aerosolized from water films and wet environments compared to terrestrial environments, where initial drying has lethal effects.